Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.ijid.2019.01.038
|View full text |Cite
|
Sign up to set email alerts
|

NTCP S267F variant associates with decreased susceptibility to HBV and HDV infection and decelerated progression of related liver diseases

Abstract: To determine potential associations of the rs2296651 variant (c.800C > T, S267F) of NTCP with HBV and HBV plus concomitant HDV infection as well as with the progression of related liver diseases. Methods: The S267F variant was genotyped by DNA sequencing in 620 HBV-infected patients and 214 healthy controls (HCs). Among the patients, 450 individuals were tested for HDV by a nested PCR assay. Logistic regression was applied to examine the association. Results: The S267F variant was found more frequently among H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 30 publications
0
26
2
Order By: Relevance
“…NTCP signals in the lysates were similar at all time points, indicating that all covalently labeled NTCP was replaced by a complete new set of NTCP molecules. We also labeled NTCP at the plasma membrane with Myrcludex B-FITC and confirmed specific binding of Myrcludex B-FITC to wild-type NTCP, yet not to a genetic variant of NTCP with a serine to phenylalanine substitution at position 267 (S267F) that is known to reduce both bile acid transport and the susceptibility to HBV and HDV infection 3,17 ( Fig. S2A-B).…”
Section: Resultsmentioning
confidence: 56%
“…NTCP signals in the lysates were similar at all time points, indicating that all covalently labeled NTCP was replaced by a complete new set of NTCP molecules. We also labeled NTCP at the plasma membrane with Myrcludex B-FITC and confirmed specific binding of Myrcludex B-FITC to wild-type NTCP, yet not to a genetic variant of NTCP with a serine to phenylalanine substitution at position 267 (S267F) that is known to reduce both bile acid transport and the susceptibility to HBV and HDV infection 3,17 ( Fig. S2A-B).…”
Section: Resultsmentioning
confidence: 56%
“…Moreover, Li, et al [15]reported a 4.4% MAF of rs2296651 among the Chinese Han population. In a more recent study among Vietnamese, the rs2296651 variant was reported in an average of 6% of the population, with a T minor allele frequency of 3% [19].…”
Section: Discussionmentioning
confidence: 95%
“…Several studies have indicated that variants of rs2296651 either increases an individual's susceptibility to HBV infection and/or its complications, makes resolution/viral clearance of the infection faster or improves the prognostic outcome of cirrhosis and HCC [15,[19][20][21][22]. The evidence of the transferability of rs2296651 associated with HBV infection has been demonstrated among the Han population [15], Taiwanese [24] and Vietnamese [19]. However, unlike our results, rs2296651 [(c.800C >T) (S267F)] has been associated with reduced HBV infection and associated hepatic complications [25].…”
Section: Discussionmentioning
confidence: 99%
“…118 The SLC10A1 S267F variant was independently associated with a decreased risk of cirrhosis and HCC in a large cohort study performed in Taiwan, 119 and these results were confirmed in later studies. 120,121 This variant has also been linked with a lower susceptibility to develop CHB. 120 These findings could have therapeutic implications, a view that is supported by an in vitro study where cyclosporine A and its analogues inhibited HBV entry into cultured hepatocytes by targeting the NTCP membrane transporter, 122 and a study in patients with chronic hepatitis delta treated with myrcludex.…”
Section: Genetic Biomarkersmentioning
confidence: 99%
“…120,121 This variant has also been linked with a lower susceptibility to develop CHB. 120 These findings could have therapeutic implications, a view that is supported by an in vitro study where cyclosporine A and its analogues inhibited HBV entry into cultured hepatocytes by targeting the NTCP membrane transporter, 122 and a study in patients with chronic hepatitis delta treated with myrcludex. 123 Some variants of the IFN lambda (IFNL) gene such as IFNL3/IFNL4 have been associated with hepatic inflammation and fibrosis in CHB and in chronic hepatitis C. 124 A noninvasive decision model named FIBROGENE, which includes clinical data and IFNL3/IFNL4, has a very high negative predictive value (> 0.96) for ruling out cirrhosis in patients with CHB.…”
Section: Genetic Biomarkersmentioning
confidence: 99%